(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Septic shock is associated with high mortality despite advances in critical care. The neutrophil-to-lymphocyte ratio (NLR) and mean platelet volume (MPV) are inexpensive inflammatory biomarkers, but the prognostic value of serial measurements remains uncertain. Objective: To evaluate the prognostic value of Day 1 and Day 5 NLR and MPV measurements, and their temporal changes, for predicting 28-day mortality in patients with septic shock. Methods: This prospective observational study included 40 adults with septic shock admitted to a tertiary intensive care unit. NLR and MPV were measured on Day 1 and Day 5 of admission. Changes in biomarker values were calculated as ΔNLR and ΔMPV. The primary outcome was 28-day mortality. Receiver operating characteristic (ROC) curve analysis was performed to assess prognostic performance. Results: Twenty-seven of 40 patients (67.5%) died within 28 days. Significant differences between survivors and non-survivors were observed for Day 1 NLR (p=0.021), Day 5 NLR (p=0.005), Day 1 MPV (p=0.015), and Day 5 MPV (p=0.002). ΔNLR was not associated with mortality (p=0.686), while ΔMPV approached statistical significance (p=0.052). Day 5 MPV demonstrated the highest discriminatory performance (AUC, 0.805), with an optimal cut-off of 11.5 fL, sensitivity of 84.6%, and specificity of 66.7%. Conclusions: Day 1 and Day 5 measurements of NLR and MPV were associated with 28-day mortality in patients with septic shock, with Day 5 MPV demonstrating the best discriminatory performance. Temporal changes in these biomarkers, particularly ΔNLR, did not provide additional prognostic value.